Computational studies of pressure distribution of flow through inline dimpled plate. Issue 1 (July 2020) - Sukardin, M Setiawan; Salam, Nasaruddin; Tarakka, Rustan; Haddade, Jalaluddin; Ihsan, Muhammad
Abstract: Dimple plates are widely used for construction and vehicles, especially in car bodies, trains, and aircraft wings. The dimples surface helps to overcome turbulent airflow around vehicles, thereby delaying the separation point and producing fewer vertices and drag. This study aims to predict the pressure distribution occurring over the plate surface with the formation of inline dimple rows on the upper back end. The test is carried out with Computational Fluid Dynamic (CFD) FLUENT program. The test model has a dimension of 300 mm in length, 100 mm in width, and dimples ratio (DR) of 0.5. Dimples are arranged inline as much as 1 to 6 rows. Upstream velocities through dimple plates range from 10 m/s to 20 m/s. The results of the study show that the minimum pressure coefficient occurs at the top front of the plate due to the flow separation that occurs at the front end of the plate. At x/L=0.25 x/L=0.5 and x/L=0.75 (before the dimples formation), a flow pattern returns to normal, this can be seen from the distribution of the relative pressure coefficient that does not change. At the measurement point x/L=0.95 (after dimples formation), there is a decrease in the pressure coefficient. This decrease occurs due to changes in flow characteristics. The pressure coefficient does not change significantly in dimple variations of 2 to 4 rows. Meanwhile, the pressure coefficient decreases with the variation of the 5 and 6-row dimples.